1996
DOI: 10.1016/0143-8166(95)00082-8
|View full text |Cite
|
Sign up to set email alerts
|

Real-time optical monitoring system for dye colour and concentration

Abstract: A system for real-time monitoring of a dye has been constructed which enables us to measure the concentration and fluctuations of the three base colours. The method is based on light attenuation theory and its principle requires three different lasers having the three base colours. The system consisted of a semiconductor laser and argon ion laser for light sources, a photodiode for a light detector and a personal computer for data processing. Detection sensitivity for the dye concentration was a few mg I I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…and uses the solvent in which the dye is dissolved in order to tune the concentration of dye. Also, it is reported that the concentration of the colorant in the dye-solvent mixture decreases with time 1 . Due to such a problem, tracking the dye concentration becomes vital and there exists few literature that addresses such problems 2 .…”
Section: Introductionmentioning
confidence: 99%
“…and uses the solvent in which the dye is dissolved in order to tune the concentration of dye. Also, it is reported that the concentration of the colorant in the dye-solvent mixture decreases with time 1 . Due to such a problem, tracking the dye concentration becomes vital and there exists few literature that addresses such problems 2 .…”
Section: Introductionmentioning
confidence: 99%